Did Indonesia achieve the MDGs goals by 2015 ? - Tosepu, Ramadhan; Effendy, Devi Savitri; Bahar, Hartati; Ali Imran Ahmad, La Ode; Sakka, Ambo; Asfian, Pitrah; Lestari, Hariati (Public Health of Indonesia, 2016)
MDGs 2015 are the program for the welfare of society. The countries that show the great achievement of MDGs goals remain the successful of the government of the countries. This paper aimed to provide the knowledge regarding the achievement of Indonesia in MDGs goals. The achievement could be seen from the distribution of poverty, Health development index, Nutritional status, maternal mortality, and Malaria status in Indonesia.